The Influence of Maternal Empowerment Through Maternal Class on Maternal Knowledge about Pregnancy Danger Signs - Rahmawati Rahmawati; Dwi Prihatin Era; Ega Ersya Urnia (Journal of Pharmaceutical and Health Research, 2023)
Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) remain serious issues related to pregnancy and childbirth. To address this problem and enhance maternal knowledge about pregnancy danger signs, innovative efforts through maternal classes are necessary. The objective of this study is to examine the influence of maternal empowerment through maternal classes on maternal knowledge about pregnancy danger signs in UPT Karangan Primary Health Center, Kutai Timur Regency. This study utilized a pre-experimental design with one-group pretest and posttest. The purpose was to assess the influence of maternal empowerment through maternal classes on maternal knowledge in UPT Karangan Primary Health Center, Kutai Timur Regency. The population consisted of 54 pregnant women who attended maternal classes in UPT Karangan Primary Health Center during the period of July 2022 to November 2022. Nonprobability sampling technique was used to select a sample of 22 pregnant women. The test statistic showed that the Sig (2-tailed) value was 0.008, which is less than α (α=0.05). Based on the analysis using the Mc Nemar test, it can be concluded that there is a significant influence between pretest and posttest scores in the first and second meetings. Maternal empowerment through maternal classes significantly enhances knowledge about pregnancy danger signs. Expert teaching and class evaluation contribute to the effectiveness of this program in reducing maternal and infant mortality rates.